Core-shell metal-organic frameworks and metal functionalization to access highest efficiency in catalytic carboxylation; Journal of Catalysis; Vol. 371 - Gong Yanyan; Yuan Ye; Chen Cheng; Zhang Pan; Wang Jichao; Zhuiykov S. Serge; Chaemchuen S. Somboon; Verpoort F. V. K. Frensis Valter Kornelius (2019, 2019)
Title screen